The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.11114/ijsss.v3i6.938
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing High Unemployment in Tajikistan

Abstract: The main aim of this paper is to identify the major determinants of unemployment in Tajikistan. As a result, three independent variables are chosen to be tested which are, lack of education, lack of skills, and low wages. The scope of the study is the population of Tajikistan and we followed the random sampling technique to collect the data. The data hence collected during April to May 2015 and a total of 390 usable questionnaires obtained. The regression results show that there is a positive and significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This situation alone can cause an increase in a social vice. Nasridini and Behrooz (2015) [16] identified social vice to include armed robbery, kidnap, internet fraudster, alcoholism among others. With this in mind, scholars conclude that the only way out of this sad situation is participation in entrepreneurship.…”
Section: Statement Of the Problemsmentioning
confidence: 99%
“…This situation alone can cause an increase in a social vice. Nasridini and Behrooz (2015) [16] identified social vice to include armed robbery, kidnap, internet fraudster, alcoholism among others. With this in mind, scholars conclude that the only way out of this sad situation is participation in entrepreneurship.…”
Section: Statement Of the Problemsmentioning
confidence: 99%
“…It affects almost all segments of society, ranging from students to retired senior citizens. Unemployment rate is an important economic indicator which can help to identify the weaknesses or the power of certain countries economic economy (Nasridini & Behrooz, 2015).…”
Section: Definition Of Covid-19 Unemployment and Economic Growthmentioning
confidence: 99%
“…They found that the growth rate of population and FDI were negatively linked to unemployment, while unemployment was not significantly affected by inflation and GDP growth. Asliddin & Gharleghi (2015) investigated what defines Tajikistan's high unemployment. They stated that low wages and educational shortages were major determinants of high unemployment in Tajikistan, both of which are positively related to unemployment.…”
Section: Theoretical Backgroundmentioning
confidence: 99%